Modern resort business of Ukraine as a socio-economic system - Shashero, A.; Molodetskiy, A.; Nikolaieva, O.; Kudelina, S. (Journal of Education, Health and Sport, 2025)
The article is devoted to the issues of presenting the modern resort business that has developed in Ukraine as a systemic organism. The article reveals the features of the resort business. The need for a comprehensive approach to its study. The resort business is considered as a system. Five subsystems of the resort business are identified. Their features are justified.